2006
DOI: 10.1063/1.2201058
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of disk- and band-like voids in dusty plasma systems

Abstract: The minimum-energy configurations of systems of multispecies charged grains of different mass and charge with an interaction potential including long-range repulsive as well as short-range attractive components are studied by molecular dynamics simulation. The grains are also subject to a radial drag force and a quadratic confining potential. It is found that central as well as band-like void regions separating grains of different species can exist as well as coexist, depending on the species parameters. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In order to understand the connection between structure and properties of these materials, the combination of TEM and theoretical calculations is very powerful. However, it is important to realize that TEM images only correspond to a two-dimensional (2D) projection of a three-dimensional (3D) object. In order to gain the necessary structural information concerning the 3D nanoassemblies, 3D TEM, so-called electron tomography, has to be performed. Recently, this technique has proven its power in the investigation of 3D nanoassemblies, especially when quantitative data, such as particle diameters or positions, are required. , 2D self-assembled systems have been theoretically studied in depth during the past decade, and the transition between 2D and 3D assemblies has been recently investigated . However, these studies are mainly based on phenomenological models, ,,− but do not yield insight concerning the underlying physical processes involved during the formation of the 3D assemblies.…”
mentioning
confidence: 99%
“…In order to understand the connection between structure and properties of these materials, the combination of TEM and theoretical calculations is very powerful. However, it is important to realize that TEM images only correspond to a two-dimensional (2D) projection of a three-dimensional (3D) object. In order to gain the necessary structural information concerning the 3D nanoassemblies, 3D TEM, so-called electron tomography, has to be performed. Recently, this technique has proven its power in the investigation of 3D nanoassemblies, especially when quantitative data, such as particle diameters or positions, are required. , 2D self-assembled systems have been theoretically studied in depth during the past decade, and the transition between 2D and 3D assemblies has been recently investigated . However, these studies are mainly based on phenomenological models, ,,− but do not yield insight concerning the underlying physical processes involved during the formation of the 3D assemblies.…”
mentioning
confidence: 99%
“…The objective of this work is to theoretically study the distribution of charged polymers in a trap potential to understand the underlying mechanisms of the structure formation in charged biomolecules. In many colloidal and plasma systems, the pattern formation is due to the presence of some short-ranged attractive forces in the system [35][36][37][38][39][40][41]. Here we show that the pattern formations can occur even in the absence of the attractive interactions, primarily due to the competing effects of the trap and the electrostatic repulsions.…”
Section: Introductionmentioning
confidence: 79%
“…This formalism would provide a useful description for the micro-structures that form in polymer colloids confined in optical traps. In recent years structural transitions in trapped colloids as well as plasmas have attracted the attention of experimentalists as well as theorists [35][36][37][38][39][40]. The colloidal and dusty plasmas have been found to form shell structures in 3D…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional self-assembled systems have been investigated in the past using a competing interaction for the pairwise potential and considering a quadratic confinement potential in order to stabilize the system formation in a closed region. The self-organization and the pattern formation were also analyzed in 2D by applying different methods. , Recently, experiments have shown that the interparticle interaction can be modeled by a pairwise competing potential in the case of self-assembled clusters of metallic nanoparticles, ,, quantum dots at the air–water interface, and colloidal clusters by depletion attraction .…”
Section: Introductionmentioning
confidence: 99%